The Effect of Electroacupuncture Therapy on Pain, Plasma β-Endorphin, and Quality of Life of Stage III Cervical Cancer Patients: A Randomized Control Trial - Wita Saraswati; Ratih Wardani; Suhatno Suhatno; Pudjo Hartono; Ario Imandiri (Medical Association of Pharmacopuncture Institute, 2021)
Background : Pain is a major complaint in cancer patients and a global problem that requires medical attention, including pain in cervical cancer. Although pharmacotherapy has been used for the treatment of cancer pain, there are still around 40% cannot be treated only with pharmacotherapy. Objectives: To determine the effects of electroacupuncture (EA) on pain in stage III cervical cancer patients. Methods : Twenty-eight stage III cervical cancer patients were divided into two groups (14 treatments and 14 controls) with randomized control trial design. The treatment group received EA with a frequency of 2/20-25 Hz at points of ST36, SP6, LI4 and LR3 for 30 minutes, while the control group did not receive EA. Both groups were given paracetamol and codeine at the same dose. Assessment was carried out by measuring pain scale (VAS), plasma β-endorphin levels, and quality of life/QoL (EORTC QLQ-C30) before and after therapy. Results : The average reduction in VAS in the treatment group (2.71 ± 1.14) compared to the control group (0.71 ± 1.33; p < 0.001), average increase in plasma β-endorphin levels in the treatment group (88.57 ± 52.46 pg/ml) compared to the control group (12.86 ± 56.76 pg/ml; p = 0.001), and in QoL, there were significant differences in symptom improvement between the treatment and control groups in the domain of fatigue, pain, insomnia and overall QoL (p < 0.05). Conclusion : Medical therapy combined with EA decreased pain scale, increased plasma β-endorphin levels, and improved the QoL for stage III cervical cancer patients.